Tre Canti. L'ascolto come pratica drammaturgica nelle performance di Agnese Banti, Diana Lola Posani e Tilia Auser (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
Agnese Banti, Tilia Hauser and Diana Lola Posani: starting from an analysis of the performances of these three Italian artists who have recently emerged on the national scene, this paper first of all sets out to analyse the ways in which certain lines of investigation relating to the field of voice studies, ecology of listening and relational and spatial dimension of sound meet the performative dimension, as well as the consequences that this meeting produces from the point of view of the creation of aesthetics and modes of fruition and the hybridisation of languages. The aim of the paper is not to trace common lines of research, but, while respecting the stylistic and aesthetic diversities of the individual paths, to try to understand what figures, narrative, relational and aesthetic modalities these lines of research are producing, first and foremost through an analysis and description of the individual works, but also by activating a dialogue with the artists on their respective working methodologies, and in particular on the question of the dramaturgical and artistic role played by the figure of listening within their practices.